EXPLORING THE FIVE-FACTOR PERSONALITY TRAITS ON THE USEFULNESS AND EASINESS PERCEPTIONS OF USING INSTAGRAM’S PAID PROMOTION - Pangaribuan, Christian Haposan; Aggraeni, Ella Intan; Sitinjak, Martinus Fieser (APPS Publications, 2018)
Instagram has become a popular tools to promote online businesses. Despite all that, not all online shop owners are aware of the purpose of the paid promotion on Instagram. Thus, the objective of this research is to find out the relationship between personality and technology acceptance to understand paid promotion on Instagram story using Big Five Factor Personality model (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism), perceived usefulness, and perceived ease of use. This research used quantitative method, while the questionnaires were distributed to 211 respondents in Jakarta, Bogor, Depok, Tangerang and Bekasi. The result of this research found that extraversion is the most influential factor towards perceived usefulness of Instagram story paid promotion. Moreover, the openness to experience is the most influential variable towards perceived ease of use. Also, perceived ease of use influences perceived usefulness.